A green analytical method for benzoyl peroxide determination by a sequential injection spectrophotometry using natural reagent extracts from pumpkin - Supharoek S. (2017)
© 2017 Elsevier B.V. A green and environmental friendly method with simple sequential injection spectrophotometry using natural reagent extract from pumpkin (Cucurbita moschata Decne) for determination of benzoyl peroxide (BPO) was developed. The maximum absorption of the yellow crude extract containing the β-carotene compound occurred at a wavelength of 450 nm. The yellow extract solution was bleached by BPO to change the color to a colorless solution. The optimum conditions of the proposed method, such as extraction solvent influence of pH, dilution of pumpkin extracts solution, aspiration volume of reagent and sample, flow reversal, incubation time, mixing coil length, and dispensing flow rate were studied and optimized. The linear calibration graph under the optimum conditions in the range of 9.4−100 mg L −1 BPO was obtained with good linearity (r 2 =9985). The limit of detection (LOD) and the limit of quantification (LOQ) were 3.9 and 9.4 mg L −1 , respectively. Relative standard deviation was achieved at less than 4% (n=7). This system provided sample throughput of 9 h −1 . Good recoveries were found between 83.42±3.34–112.29±3.49%. The system was successfully employed as a natural reagent extract from pumpkin for determination of BPO in acne treatment samples. Also, the results agreed well with those obtained from the HPLC-UV method.